CULTURE IN THE THEORY OF INTERNATIONAL RELATIONS: REALISTIC DIRECTION - Фабрика, А. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article considers the role assigned to culture in a realistic approach to the analysis of international relations. As a result of the study, aspects of international politics have been identified in which culture is given importance. In particular, culture is used as one of the ways to change the power relations between states. From the standpoint of a realistic approach, it is the struggle for power in the international arena that explains the most tangible external influences on the culture of a particular society today.